Analisis Penanganan Politik Uang Ditinjau dari Undang-Undang Pilkada - I Wayan Febrianto; Ida Ayu Putu Widiati; Luh Putu Suryani (Jurnal Interpretasi Hukum, 2020)
Money politics in the regional elections lately has become one of the things that have attracted public attention. Money politics is carried out to get a lot of votes and control the votes in the regional elections. Money politics can have a negative impact on prospective regional election participants. This research was conducted with the aim of describing the regulation of money politics prohibition in the regional elections and the sanctions for regional election candidate participants who commit money politics. This research was conducted using the normative legal method. This research showed that the regulation regarding the prohibition of money politics in regional elections is regulated in Law Number 10 of 2016 concerning the regional elections. In addition, the sanctions for candidates for regional elections who commit money politics are regulated in Law Number 10 of 2016 as amended from Law Number 8 of 2015 concerning the regional elections. Candidates for regional elections who are caught engaging in money politics will be subject to a minimum of 36 months imprisonment and a maximum of 72 months, as well as a minimum fine of IDR 200,000,000 (two hundred million rupiah) and a maximum of IDR. 1,000,000,000 (one billion rupiah).